Pengembangan Kebijakan Penyelenggaraan Haji Berbasis Pada Kepentingan Jamaah - Muchamad Ikbal; Aden Rosadi; Usep Saepullah; Nuryamin Nuryamin; Nurul Hudayanti Mahas (Yayasan Cendekia Gagayunan Indonesia, 2025)
This research discusses the development of policies for the implementation of the hajj in Indonesia that is oriented towards the interests of pilgrims. As the country with the largest number of pilgrims in the world, Indonesia faces various challenges in providing efficient, accountable, and responsive services. The purpose of this study is to analyze the implementation of the Hajj implementation policy based on the regulatory framework, especially Law No. 8 of 2019, as well as evaluate the effectiveness of its implementation in fulfilling the rights of pilgrims. This study uses a qualitative approach with a literature study method. The analysis was carried out on relevant policy documents, regulations, evaluative reports, and academic literature. The theoretical approach of public policy and excellent service is used as a basis for analysis in examining the dimensions of public services, the development of hajj officers, and fund governance by the Hajj Financial Management Agency (BPKH). The results of the study show that although there has been some progress in regulatory and institutional aspects, challenges such as complex bureaucracy, limited human resource capacity, and lack of transparency and public participation are still the main obstacles. However, there is potential for improvement through systemic reforms that emphasize management transparency, increased professionalism of officers, and the involvement of pilgrims in the evaluation process. In conclusion, the policy orientation that is in favor of the pilgrims not only ensures the safe and comfortable implementation of the hajj, but also reflects the state's commitment to fulfilling the constitutional rights of citizens. The strategic recommendations in this study are expected to be constructive input for policy makers in realizing more inclusive and sustainable Hajj governance.